2008
DOI: 10.1002/qj.313
|View full text |Cite
|
Sign up to set email alerts
|

The ensemble Kalman filter in an operational regional NWP system: preliminary results with real observations

Abstract: ABSTRACT:The ensemble Kalman filter (EnKF) has been widely tested as a possible candidate for the next generation of meteorological and oceanographic data assimilation algorithms. While a number of tests with models of varying realism have been successfully performed, the EnKF has been seldom evaluated in an operational regional NWP environment at realistic spatial resolution. In this work one particular EnKF implementation (Local Ensemble Transform Kalman Filter, LETKF) has been implemented and its performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
(40 reference statements)
1
31
0
Order By: Relevance
“…This larger value than the one used in the previous study (700 km: Bonavita et al, 2008) has been found to provide more accurate analysis and forecasts. Following Szunyogh et al (2008), the influence of each observation on the analysed grid point is decreased with its geophysical distance r through multiplication of the R −1 observation error matrix entries in Eqs.…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 59%
See 4 more Smart Citations
“…This larger value than the one used in the previous study (700 km: Bonavita et al, 2008) has been found to provide more accurate analysis and forecasts. Following Szunyogh et al (2008), the influence of each observation on the analysed grid point is decreased with its geophysical distance r through multiplication of the R −1 observation error matrix entries in Eqs.…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 59%
“…Differently from Bonavita et al (2008), specific humidity has been added to the set of control variables in addition to temperature, zonal and meridional wind components and surface pressure. The analysis is now performed on the prognostic model's 40 vertical levels reaching up to 10 hPa, at the same horizontal resolution.…”
Section: Ensemble Data Assimilation At Cnmcamentioning
confidence: 99%
See 3 more Smart Citations